Risks associated with pathogenic fungi isolated from surgical centers, intensive care units, and materials sterilization center in hospitals. Risks associated with pathogenic fungi isolated from critical hospital areas. (5th February 2020) - de Oliveira, Mayk Teles; Batista, Nathany Kelly Ribeiro; Gil, Eric de Souza; Silva, Maria do Rosário Rodrigues; Costa, Carolina Rodrigues; Bara, Maria Teresa Freitas; Torres, Ieda Maria Sapateiro
Abstract: The hospital environment requires special attention to air quality, since it needs to be healthy for the protection of patients and health professionals in order to prevent them against hospital infections. The objective of this study was to isolate, identify and evaluate the susceptibility profile of isolated fungi from two hospitals. For air sampling the impaction (Spin Air, IUL ® ) and passive sedimentation methods were used. For the isolation of fungi from surfaces, contact plates (RODAC ® ) were used. The identification of the fungi was performed by observing the macroscopic and microscopic aspects of the colonies, whereas for better visualization of fruiting structures, the microculture technique was performed on slides. To evaluate the susceptibility profile, the broth microdilution test recommended by CLSI was performed. Thirty-five isolates were identified: Aspergillus flavus (12), Aspergillus fumigatus (11), Aspergillus niger (1), Aspergillus terreus (2), Penicillium spp. (7), and Fusarium spp. (2) in the hospitals evaluated. All isolates had a minimum inhibitory concentration (MIC) more than 128 μg/ml for fluconazole; 0.5 to 4.0 μg/ml for amphotericin B (hospital 1), and all isolates from haospital 2 had MIC ≥2.0 μg/ml. In hospital 1, MIC for posaconazole ranged from 0.25 μg/ml to ≥32 μg/ml, and hospital 2 ranged from 0.5 to 1.0 μg/ml. The monitoring and evaluation of air quality and surfaces are essential measures for prevention and control of hospital infections, as these microorganisms are becoming increasingly resistant to antimicrobial agents, thus making treatment difficult, especially in immunocompromised individuals.